STRATEGI KOMUNIKASI PEMASARAN PARIWISATA KEMARITIMAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI PULAU BANYAK - Elok Perwirawati; Juprianto Juprianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Aceh Singkil is one of the regencies in Nanggroe Aceh Darussalam Province that is rich in marine tourism, nature and culture. One of the popular tourism objects in this place is Banyak Island. Being well known by both local and international tourists, this tourist destination needs the right strategy. Through coordination done by government tourism office and youth and sports service of Aceh Singkil Regency, tourism communication strategy is arranged as an effort to improve the tourists’ visit in Banyak Island. This research was conducted by using descriptive-qualitative approach in which the data were collected by interview to the related parties. This research aims at : (1) knowing the maritime tourism marketing communication strategy done by government tourism office and youth and sports service of Aceh Singkil Regency in improving the tourists’ visit in Banyak Island, (2) knowing the supporting and inhibiting factors of the maritime tourism marketing communication strategy done by government tourism office and youth and sports service of Aceh Singkil Regency in improving the tourists’ visit in Banyak Island. Research findings show that the strategy of maritime tourism marketing communication done by government tourism office and youth and sports service of Aceh Singkil Regency in improving the tourists’ visit in Banyak Island are by advertising, event, publicity, and word of mouth marketing. The supporting factors of communication marketing are potential attractions for dance culture (Adok dance, Umbrella dance) and tomb of Makam syekh Abdurauf As-Singkily as national Islamic treasure. Meanwhile, the inhibiting factors, one of them, is lack of crossing transportation for tourists to visit Banyak Island